CHOOSING APPROPRIATE TECHNIQUES FOR QUANTIFYING GROUNDWATER RECHARGE - Scanlon B.R.; Healy R.W.; Cook P.G. (My University, 2002)
Various techniques are available to quantify recharge; however, choosing appropriate techniques is often difficult. Important considerations in choosing a technique include space/time scales, range, and reliability of recharge estimates based on different techniques; other factors may limit the application of particular techniques. The goal of the recharge study is important because it may dictate the required space/time scales of the recharge estimates. Typical study goals include water-resource evaluation, which requires information on recharge over large spatial scales and on decadal time scales; and evaluation of aquifer vulnerability to contamination, which requires detailed information on spatial variability and preferential flow. The range of recharge rates that can be estimated using different approaches should be matched to expected recharge rates at a site. The reliability of recharge estimates using different techniques is variable. Techniques based on surface-water and unsaturated-zone data provide estimates of potential recharge, whereas those based on groundwater data generally provide estimates of actual recharge. Uncertainties in each approach to estimating recharge underscore the need for application of multiple techniques to increase reliability of recharge estimates.
Keywords: GROUNDWATER RECHARGE/WATER BUDGET; NUMERICAL MODELING; ARID REGIONS; UNSATURATED ZONE; GROUNDWATER AGE